Uppfattningar om centrala Luleås luftkvalité och miljö : En studie för att uppskatta betalningsviljan - Larsson, Victor; Persson, Terese (2015)
This thesis aims to investigate the attitudes toward the air quality and accessibility in downtown Luleå, Sweden. Furthermore, it aims to investigate what factors influence the WTP for lowering nitrogen dioxide levels. A CVM was employed, and 386 visitors of downtown Luleå responded to the survey. The WTP for better air quality was elicited in a setting that was not purely hypothetical. Respondents were also asked to vote regarding the action plan in a hypothetical referendum. Responses were analyzed using OLS and Probit models. Results indicate a positive WTP, with a mean of 1235 SEK/year. The referendum support of the action plan was 63,2%. Significant predictors of WTP were found to be age, income, gender, number of adults in the household, problem recognition and visiting rates. The significant factors affecting the probability of a yes vote were the visiting frequency, environmental concern, usual means of transportation and problem recognition. Validerat; 20150623 (global_studentproject_submitter)